PENGARUH JENIS BAHAN DASAR DAN DOSIS PUPUK ORGANIK CAIR TERHADAP PERTUMBUHAN DAN HASIL BUNCIS (Phaseolus vulgaris L.) - Made Deviani Duaja (Bioplantae, 2013)
Snap beans (Phaseolus vulgaris L.) is one of the important legumes vegetable crops, and as a good source of protein. More attention has been done to secure high yield and good quality of snap bean and the key role through fertilization with organic fertilizers. This research purpose is to study the effect of various basic materials and doses of liquid organic fertilizers on growth and yield of two snap bean varieties. This experiment was carried out in Teaching and Research Farm, Agriculture Faculty, Jambi University. The research was design in Randomized Blok Design (RBD) the factor were combination between basic materials of liquid organic fertilizers (Gliricidia sepium, Crotolaria juncea, Leucaena leucocephala and Cromolaena odorata), and doses of liquid organic fertilizers. All the treatment replicate 3 times. The treatments were without organic fertilizer but inorganic fertilizers (NPK 16-16-16), Gliricidia sepium (doses 15.0, 20.0 and 25.0 ml/plant), Crotolaria juncea (doses 15.0, 20.0 and 25.0 ml/plant), Leucaena leucocephala (doses 15.0, 20.0 and 25.0 ml/plant), Cromolaena odorata (doses 15.0, 20.0 and 25.0 ml/plant). Data was subjected to Anova and mean comparisons were done using the Least Significat difference (LSD). The result showed there was significant difference effect between the treatments. The highest number of snap bean pod yield was achieved at Crotolaria juncea 25 ml/plant but there are no significant differences with Cromolaena odorata at 25 ml/plant and control . Keywords: Snap, Crotolaria, Leucaena, Cromolaena.